Using Transcranial Electrical Stimulation in Audiological Practice: The Gaps to Be Filled - Nooristani, Mujda; Augereau, Thomas; Moïn-Darbari, Karina; Bacon, Benoit-Antoine; Champoux, François (Frontiers in Human Neuroscience, 2021)
The effects of transcranial electrical stimulation (tES) approaches have been widely studied for many decades in the motor field, and are well known to have a significant and consistent impact on the rehabilitation of people with motor deficits. Consequently, it can be asked whether tES could also be an effective tool for targeting and modulating plasticity in the sensory field for therapeutic purposes. Specifically, could potentiating sensitivity at the central level with tES help to compensate for sensory loss? The present review examines evidence of the impact of tES on cortical auditory excitability and its corresponding influence on auditory processing, and in particular on hearing rehabilitation. Overall, data strongly suggest that tES approaches can be an effective tool for modulating auditory plasticity. However, its specific impact on auditory processing requires further investigation before it can be considered for therapeutic purposes. Indeed, while it is clear that electrical stimulation has an effect on cortical excitability and overall auditory abilities, the directionality of these effects is puzzling. The knowledge gaps that will need to be filled are discussed.